👤

Subtract as indicated.
1.) (a - 2) - (a - 9)
2.) (b - 7) - (4b - 2)
3.) (b5 - b³) - (b⁴ - b²)

simplify each.
1. a5 • a7
2. (a⁴)5
3. (5e6)(-4e⁴)
4. (-7a⁴)(3a²)²



Sagot :

Answer:

1.

[tex] = (a - 2) - (a - 9) \\ = a - 2 - a + 9 \\ = 7[/tex]

2.

[tex] = (b - 7) - (4b - 2) \\ = b - 7 - 4b + 2 \\ = - 3b - 7 + 2 \\ = - 3b - 5[/tex]

3.

[tex] = (b5 - b {}^{3} ) - (b {}^{4} - b {}^{2} ) \\ = (5b - b {}^{3} ) - b {}^{4} + b {}^{2} \\ = 5b - b {}^{3} - b {}^{4} + b \\ = - b {}^{4} - b {}^{3} + b {}^{2} + 5b[/tex]

Step-by-step explanation:

1.

[tex] = a5 \times a7 \\ = a {}^{1} \times 35a {}^{1} \\ = a {}^{1 + 1} \times 35 \\ = a {}^{2} \times 35 \\ = 35a {}^{2} [/tex]

2.

[tex] = (a {}^{4} )5 \\ = 5a {}^{4} [/tex]

3.

[tex] = (5e6)( - 4e {}^{4} ) \\ = ( - 30e) \times ( - 4e {}^{4} ) \\ = - 30e \times 4e {}^{4} \\ = - 120e {}^{5} [/tex]

4.

[tex] = ( - 7a {}^{4} )(3a {}^{2} ) {}^{2} \\ = - 7a {}^{4} \times 9a {}^{4} \\ = - 63a {}^{8} [/tex]